2015
DOI: 10.3748/wjg.v21.i13.3928
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of PIVKA-II and alpha-fetoprotein in hepatitis B virus-associated hepatocellular carcinoma

Abstract: Serum PIVKA-II might be a better tumor marker than AFP, and its combination with AFP may enhance the early detection of HCC in patients with CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 37 publications
7
60
0
Order By: Relevance
“…In recent years, PIVKA-II is considered to be a novel serological marker for HCC. 6,23 Our results indicated that PIVKA-II was significantly higher in AFP-NHCC patients and were useful for distinguishing AFP-NHCC from cirrhosis and controls, and the sensitivity was 65.4%, the specificity was 84.6%, which was consistent with previous research results. 23 In our research, miR-363-5p was the most effective indicator (AUC = 0.901) for the diagnosis of AFP-NHCC than miR-765 (AUC = 0.838) and PIVKA-II (AUC = 0.749), but its sensitivity (78.5%) was unsatisfactory.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In recent years, PIVKA-II is considered to be a novel serological marker for HCC. 6,23 Our results indicated that PIVKA-II was significantly higher in AFP-NHCC patients and were useful for distinguishing AFP-NHCC from cirrhosis and controls, and the sensitivity was 65.4%, the specificity was 84.6%, which was consistent with previous research results. 23 In our research, miR-363-5p was the most effective indicator (AUC = 0.901) for the diagnosis of AFP-NHCC than miR-765 (AUC = 0.838) and PIVKA-II (AUC = 0.749), but its sensitivity (78.5%) was unsatisfactory.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that serum levels of miR‐363‐5p and miR‐765 in patients with AFP‐NHCC were significantly higher than those in cirrhosis and controls and were related to differentiation, tumor size, and TNM stage, confirming that they are oncogenes in HCC. In recent years, PIVKA‐II is considered to be a novel serological marker for HCC . Our results indicated that PIVKA‐II was significantly higher in AFP‐NHCC patients and were useful for distinguishing AFP‐NHCC from cirrhosis and controls, and the sensitivity was 65.4%, the specificity was 84.6%, which was consistent with previous research results .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using PIVKA-II in combination with AFP has been reported to improve accuracy [14]. Other studies looking exclusively at hepatitis B infected individuals suggest PIVKA-II is superior to AFP, and that the combination of both measures may enhance early detection [15]. A recent study comprising roughly 2 000 participants concluded that 230 HCC cases would have been neglected if using AFP alone, and that PIVKA-II levels increased over a year before image discovery [16].…”
Section: Performance Of Pivka-ii As a Hcc Tumour Markermentioning
confidence: 99%